2022
DOI: 10.3847/psj/ac6d65
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Overturning Circulation on Dry, Tidally Locked Rocky Planets Is Mainly Driven by Radiative Cooling

Abstract: In this study, we examine the driving mechanism for the atmospheric overturning circulation on dry, tidally locked rocky planets without the condensation of water vapor or other species. We find that the main driving process is the radiative cooling of CO2 (or other noncondensable greenhouse gases) rather than CO2 greenhouse warming or stellar radiation. Stellar radiation is the ultimate mechanism but not the direct mechanism. Due to the combination of the uneven distribution in the stellar radiation and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…The dynamics obtained in our simulation with a modern Venuslike atmosphere substantially differ from previous simulations of tidally locked terrestrial planets with Earth-like atmospheres (surface pressure of 1 bar) but with similar stellar irradiation and rotation rate values to this work. These studies consistently found a single equatorial superrotation jet located at ∼500 mbar with speeds on the order of dozens of m s −1 (Penn & Vallis 2018 ;Hammond, Tsai & Pierrehumbert 2020 ;Hammond & Lewis 2021 ;Sergeev et al 2022 ;Wang & Yang 2022 ). Ho we ver, at least two distinct dynamical regimes can occur in these worlds (e.g.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 87%
“…The dynamics obtained in our simulation with a modern Venuslike atmosphere substantially differ from previous simulations of tidally locked terrestrial planets with Earth-like atmospheres (surface pressure of 1 bar) but with similar stellar irradiation and rotation rate values to this work. These studies consistently found a single equatorial superrotation jet located at ∼500 mbar with speeds on the order of dozens of m s −1 (Penn & Vallis 2018 ;Hammond, Tsai & Pierrehumbert 2020 ;Hammond & Lewis 2021 ;Sergeev et al 2022 ;Wang & Yang 2022 ). Ho we ver, at least two distinct dynamical regimes can occur in these worlds (e.g.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 87%
“…Atmospheric compositions should also have impacts on the LEC. Ding & Wordsworth (2019) showed that excluding greenhouse gases from the atmosphere would decrease the day-night temperature contrast and wind speeds; Wang & Yang (2022) showed that the atmospheric circulation in a pure N 2 atmosphere without any greenhouse gas is very weak. They suggested that the potential and kinetic energy would be smaller in an atmosphere without any greenhouse gas.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For tidally locked terrestrial planets, especially slowly rotating ones, the Eulerian mean should match the monotonically decreasing stellar radiation and temperature along an arbitrary direction from dayside to nightside (Figure 2(d)). So, for slowly rotating, tidally locked terrestrial planets, the tidally locked coordinates are employed in this study, similar to that used in previous studies (e.g., Koll & Abbot 2015Ding & Pierrehumbert 2020;Ding & Wordsworth 2020;Hammond & Lewis 2021;Sergeev et al 2022;Turbet et al 2022;Wang & Yang 2022). In the tidally locked coordinates, the nominal "north/south pole" is the substellar/antistellar point, the tidally locked latitude lines are a series of concentric circles around the substellar point, and the tidally locked longitude lines are the great circles linking the substellar and antistellar points (Figure 2(b)).…”
Section: Lec In Tidally Locked Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation